A toddler PCV booster dose following 3 infancy priming doses increases circulating serotype-specific IGG levels but does not increase protection against carriage. Issue 20 (11th May 2018) - Dagan, Ron; Ben-Shimol, Shalom; Simell, Birgit; Greenberg, David; Porat, Nurith; Käyhty, Helena; Givon-Lavi, Noga
Abstract: Background: We compared PCV7 serological response and protection against carriage in infants receiving 3 doses (2, 4, 6 months; 3+0 schedule) to those receiving a booster (12 months; 3+1). Methods: A prospective, randomized controlled study, conducted between 2005 and 2008, before PCVs were implemented in Israel. Healthy infants were randomized 1:1:1 to receive 3+1, 3+0 and 0+2 (control group; 12, 18 months doses). Nasopharyngeal/oropharyngeal swabs were obtained at all visits. Serum serotype-specific IgG concentrations and opsonic activities (OPA) were measured at 2, 7, 13 and 19 months. This study was registered with Current Controlled Trials, Ltd. ISRCTN28445844. Results: Overall, 544 infants were enrolled: 3+1 (n = 178), 3+0 (n = 178) and 0+2 (n = 188). Post-priming (7 months), antibody concentrations were similar in both groups, except for serotype 18C (higher in 3+0). Post-booster (13, 19 months), ELISA and OPA levels were significantly higher in 3+1 than in 3+0 group. Nasopharyngeal/oropharyngeal cultures were positive for Streptococcus pneumoniae in 2673 (54.3%) visits. Acquisition rates (vaccine and non-vaccine serotypes) were similar for 3+1 and 3+0 groups at 7–30 months and for 0+2 group at 19–30 months. Conclusions: PCV7 booster after 3 priming doses increased substantially IgG concentrations but did not further reduced vaccine-serotype nasopharyngeal acquisition, suggesting that protection from pneumococcal carriage does not depend primarily on serum IgG.